2014
DOI: 10.1371/journal.pone.0111218
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Study of Avian Influenza in One District of Guangzhou, 2013

Abstract: Since Feb, 2013, more than 100 human beings had been infected with novel H7N9 avian influenza virus. As of May 2013, several H7N9 viruses had been found in retail live bird markets (LBMs) in Guangdong province of southern China where several human cases were confirmed later. However, the real avian influenza virus infection status especially H7N9 in Guangzhou remains unclear. Therefore, a cross-sectional study of avian influenza in commercial poultry farms, the wholesale LBM and retail LBMs in one district of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…In order to control and prevent the spread of H5N1 and H9N2 viruses in chickens, a detailed understanding of infection patterns at bird and flock‐level is required. It is hypothesized that different poultry species and different poultry husbandry systems might play different roles in the transmission and maintenance of avian influenza viruses (Alexander, 2000; Zhang et al., 2014). The study presented here quantifies the extent of H5 and H9 virus circulation on backyard chicken farms, and on commercial broiler and layer chicken farms in two representative districts of Bangladesh.…”
Section: Introductionmentioning
confidence: 99%
“…In order to control and prevent the spread of H5N1 and H9N2 viruses in chickens, a detailed understanding of infection patterns at bird and flock‐level is required. It is hypothesized that different poultry species and different poultry husbandry systems might play different roles in the transmission and maintenance of avian influenza viruses (Alexander, 2000; Zhang et al., 2014). The study presented here quantifies the extent of H5 and H9 virus circulation on backyard chicken farms, and on commercial broiler and layer chicken farms in two representative districts of Bangladesh.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found prevalence to be especially high where heavy contamination occurs and on visibly dirty, moist, or difficult‐to‐clean surfaces (Indriani et al., 2010; Trock, Gaeta, Gonzalez, Pederson, & Senne, 2008), for example along the wall‐floor junctions, cracks and holes. However, one of the disadvantages of using ES constitutes the possibility of detecting viruses which are not currently present in the birds at the time due to accumulation and persistence within the environment (Lang, Kelly, & Runstadler, 2008; Zhang et al., 2014).…”
Section: Resultsmentioning
confidence: 99%
“…13,14 Various studies have been conducted targeting the animal-human interface and have reported different routes of human exposure to AIVs identifying potential host determinants that favored persistence of virus. [4][5][6][7][8][9][15][16][17] Early preparedness for global pandemics has become an important public health task. Preparedness includes identification of determinants of disease spread at animal-human interface and ultimately recognizing areas to implement disease prevention and outbreak control.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, traditional small‐scale poultry production systems have been transformed into industrial integrated operations in most parts of the world including Asia . Various studies have been conducted targeting the animal‐human interface and have reported different routes of human exposure to AIVs identifying potential host determinants that favored persistence of virus …”
Section: Introductionmentioning
confidence: 99%